(untitled) (Al-Qamar, 2021)
It is well known that Hazrat Muhammad (ﷺ) has a multidimensional characteristics personality. His brilliant Seerah of both era (Makki and Madni) contains an excellent guideline even before his Prophethood. One-fold of his golden Seerah is his participation in Fijār, battle which consists of on several positive aspects and it is parable for young men. This research sketches the historical background of battle Fijār, its strengths, and results. The second fold of the study discusses the egotism, prejudice and out dated traditions of Arabs. Although, the battle is named, Fijār but the tribe of Holy Prophet (ﷺ) was on the right. Besides this, his character, seriousness and behavior show the strength of his personality and provides a role model for the youth. The study is helpful to highlight the contribution of Hazrat Muhammad (ﷺ) in Fijār battle.